Three concepts of a nation: Originality, kidnapping & utopia (based on “Comentarios reales”- the Royal Commentaries”- written by the Inca Garcilaso de la Vega) - Ward, Thomas (2019)
This article examines different concepts of nation that range from the ethnic, modern, and utopian. It outlines the evolution of the meaning of the word nation from the Renaissance to the 21st century and distinguishes between the nation and the nation-state, the latter kidnapping the role formerly held by the former. To understand the concept during the Renaissance, Inca Garcilaso’s Royal Commentaries will offer background as will several period dictionaries. To understand the concept from the nineteenth century on, the article considers the theories of Benedict Anderson and Eric Hobsbawm, as well as Mario Vargas Llosa’s ideas on the topic. Some conclusions applicable to Peru will be drawn.